2018
DOI: 10.1002/hep.30123
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ledipasvir–Sofosbuvir With or Without Ribavirin for Chronic Hepatitis C in Children Ages 6‐11

Abstract: Currently, there are no interferon-free treatments available for hepatitis C virus (HCV)-infected patients younger than 12 years. We evaluated the safety and effectiveness of the all-oral regimen ledipasvir-sofosbuvir ± ribavirin in HCV-infected children aged 6 to<12 years. In an open-label study, patients aged 6 to <12 years received ledipasvir 45 mg-sofosbuvir 200 mg as two fixed-dose combination tablets 22.5/100 mg once daily, with or without ribavirin, for 12 or 24 weeks, depending on HCV genotype and cirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 25 publications
4
93
0
2
Order By: Relevance
“…In addition, no patient interrupted or modified ribavirin dosing because of an adverse event of low hemoglobin. In the study by Murray et al, 2 pediatric patients aged 6 to 11 years with GT3 infection who received ledipasvir‐sofosbuvir plus ribavirin similarly did not experience hematologic laboratory abnormalities despite treatment with ribavirin …”
Section: Discussionmentioning
confidence: 98%
“…In addition, no patient interrupted or modified ribavirin dosing because of an adverse event of low hemoglobin. In the study by Murray et al, 2 pediatric patients aged 6 to 11 years with GT3 infection who received ledipasvir‐sofosbuvir plus ribavirin similarly did not experience hematologic laboratory abnormalities despite treatment with ribavirin …”
Section: Discussionmentioning
confidence: 98%
“…A 12‐week course is recommended for patients without cirrhosis; 24 weeks is recommended for those with compensated cirrhosis. Three clinical trials supporting the approval of ledipasvir/sofosbuvir in the pediatric population aged ≥ 3 years demonstrated high SVR12 rates comparable to those observed in adults . Limited real‐world data further corroborate these findings …”
Section: Hcv In the Pediatric Populationmentioning
confidence: 96%
“…So, what have we learned from the ZIRCON study and from the results of the other clinical trials on the use of DAAs in children and adolescents with chronic HCV infection? First, across the different studies the adult dosing for adolescents and, for sofosbuvir and ledipasvir, half the dose used in adults for children ages 6‐11 years, resulted in comparable plasma exposures to those found in the phase II and phase III clinical trials in adults with chronic HCV infection . Second, all of the studies showed excellent efficacy (SVR12) in children and adolescents with chronic HCV infection independently of age, treatment history, degree of liver fibrosis, and treatment duration .…”
mentioning
confidence: 93%
“…First, across the different studies the adult dosing for adolescents and, for sofosbuvir and ledipasvir, half the dose used in adults for children ages 6‐11 years, resulted in comparable plasma exposures to those found in the phase II and phase III clinical trials in adults with chronic HCV infection . Second, all of the studies showed excellent efficacy (SVR12) in children and adolescents with chronic HCV infection independently of age, treatment history, degree of liver fibrosis, and treatment duration . Third, the safety profile of these treatments was excellent in children and adolescents …”
mentioning
confidence: 94%
See 1 more Smart Citation